Предмет: Математика,
автор: malikazaripova
1)3(x+2)=4x+1
2)4(x-2)= -(3x-6)
Помогите пожалуйста.
Ответы
Автор ответа:
0
1)3(х+2)=4х+1
3х+6=4х+1
3х-4х=1-6
-х=-5
х=5
2)4(х-2)=-(3х-6)
4х-8=-3х+6
4х+3х=6+8
7х=14
х=2
3х+6=4х+1
3х-4х=1-6
-х=-5
х=5
2)4(х-2)=-(3х-6)
4х-8=-3х+6
4х+3х=6+8
7х=14
х=2
Автор ответа:
0
вроде так
Автор ответа:
0
СПАСИБО!!!!!!! ОГРОМНОЕ
Автор ответа:
0
незачто
Похожие вопросы
Предмет: Математика,
автор: nurlanasilzhan2010
Предмет: Немецкий язык,
автор: koknad123
Предмет: Математика,
автор: pilulana3
Предмет: История,
автор: edik77748
Предмет: Алгебра,
автор: Sergey4677